2022
DOI: 10.1097/cad.0000000000001458
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio predicts therapy outcomes of transarterial chemoembolization combined with tyrosine kinase inhibitors plus programmed cell death ligand 1 antibody for unresectable hepatocellular carcinoma

Abstract: The objective is to assess the predictive value of preoperative biochemical markers, expressed as neutrophil-to-lymphocyte ratio (NLR), in patients with unresectable hepatocellular carcinoma (uHCC) receiving a combination of tailored tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) plus transarterial chemoembolization (TACE). A total of 95 patients with uHCC treated with TACE + TKIs + ICIs in our hospital between March 2018 and October 2021 were included in this retrospective study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Recently, the TACE-ICIs-MTT combination regime has been widely used, covering a majority of patients in BCLC stage B and C, and achieved impressive therapeutic results. [11][12][13] While some studies have indicated that the Neutrophil-to-Lymphocyte Ratio (NLR) can predict the prognosis of patients undergoing this combination therapy, 31,32 the level of evidence supporting this remains relatively low. In our study, comparisons were made between CRAFITY and other inflammatory markers, and the results indicated that CRAFITY exhibited superior predictive performance in the treatment regime.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the TACE-ICIs-MTT combination regime has been widely used, covering a majority of patients in BCLC stage B and C, and achieved impressive therapeutic results. [11][12][13] While some studies have indicated that the Neutrophil-to-Lymphocyte Ratio (NLR) can predict the prognosis of patients undergoing this combination therapy, 31,32 the level of evidence supporting this remains relatively low. In our study, comparisons were made between CRAFITY and other inflammatory markers, and the results indicated that CRAFITY exhibited superior predictive performance in the treatment regime.…”
Section: Discussionmentioning
confidence: 99%